Transforming Meningoencephalitis Diagnosis: A Study of Filmarray ME Panel in a North Indian Tertiary Care Centre - Puneet Bhatt; Vandan Shilimkar; Jyoti Tewatia; Santosh Karade (Journal of Pure and Applied Microbiology)
Meningoencephalitis is a severe condition requiring rapid and accurate diagnosis for effective management. Traditional culture methods often fail to detect certain pathogens, leading to delayed treatment. This study was conceptualized with an aim to assess the BioFire FilmArray Meningitis/Encephalitis (ME) Panel as a first-line diagnostic tool. A total of 147 patients (91 males and 56 females) with suspected meningoencephalitis were included. Cerebrospinal fluid (CSF) samples were analyzed using the FilmArray ME Panel and results were compared with traditional culture methods. The BioFire FilmArray ME Panel detected pathogens in 14 out of 147 CSF samples, yielding a positivity rate of 9.52%. Detected pathogens included Cytomegalovirus (03), Streptococcus pneumoniae (03), HSV1 (02), E. coli K1 (01), Enterovirus (01), Haemophilus influenzae (01), HHV6 (01), Parechovirus (01), and Varicella Zoster Virus (01). In contrast, traditional culture methods detected pathogens in only 7 cases, highlighting the panel’s superior sensitivity and underscoring the limitations of traditional methods. The ME Panel’s ability to deliver accurate results from just 200 microliters of CSF and the rapid turnaround time of just 1 hour highlights its efficiency in providing critical diagnostic information from small sample volumes. The study also assessed the impact of CSF volume, with nearly one-third of samples being 0.5 mL, noting that the panel requires only 200 microliters to provide comprehensive results. The BioFire FilmArray ME Panel significantly outperformed traditional culture methods in detecting a wide range of pathogens in CSF samples, even with minimal sample volume. Its rapid and accurate diagnostics improve early diagnosis and patient management in meningoencephalitis, supporting its integration into routine clinical practice.